"The Future of Archaeology Is Antiracist": Archaeology in the Time of Black Lives Matter. Issue 2 (April 2021) - Flewellen, Ayana Omilade; Dunnavant, Justin P.; Odewale, Alicia; Jones, Alexandra; Wolde-Michael, Tsione; Crossland, Zoë; Franklin, Maria
Abstract : This forum builds on the discussion stimulated during an online salon in which the authors participated on June 25, 2020, entitled "Archaeology in the Time of Black Lives Matter, " and which was cosponsored by the Society of Black Archaeologists (SBA), the North American Theoretical Archaeology Group (TAG), and the Columbia Center for Archaeology. The online salon reflected on the social unrest that gripped the United States in the spring of 2020, gauged the history and conditions leading up to it, and considered its rippling throughout the disciplines of archaeology and heritage preservation. Within the forum, the authors go beyond reporting the generative conversation that took place in June by presenting a road map for an antiracist archaeology in which antiblackness is dismantled.